The Modern Nation-State in Egypt as a Continuation of Colonialism: The Palestinian Cause as a Case Study - A Qader (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
This study addresses a persistent gap in the literature: the absence of a causal explanation for the relationship between the values of the modern nation-state and the doctrine of Al-Wala' wal-Bara' (“Loyalty and Disavowal”) in Egyptian foreign policy. Analytically, it seeks to deconstruct the impact of secular nationalism on shifts in Egyptian foreign policy decision-making regarding the Gaza war (2023–2026). Methodologically, the study adopts a case-study approach, employing content analysis techniques alongside recently declassified intelligence documents to ensure source validity. The theoretical framework integrates Benedict Anderson's theory of the Imagined Community with Selectorate Theory to theorize the clash between transnational religious principles and the sovereignty of the modern nation-state. The causal findings reveal that the decline in doctrinal solidarity stems from the functional logic of the deep state apparatus, which defines national interest in terms of regime survival contingent upon external support. The study's substantive contribution lies in an explanatory model that enriches international relations and Islamic political studies by clarifying how religious ideology becomes subordinated to the structure of the modern state.